IMPLEMENTASI ELECTRONIC GOVERNMENT MELALUI PROGRAM PENERIMAAN PESERTA DIDIK BARU (PPDB) ONLINE SEBAGAI UPAYA PENINGKATAN PELAYANAN PENDIDIKAN KOTA BEKASI - Abdul Muis; Rizky Riyadi; Dila Novita (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
The development of information technology has entered various fields, one of which is the use of information technology and telecommunications in public services in the field of education. Based on the Ministry of Education and Culture No. 51 of 2018 concerning the improvement of online New Student Admission which makes it easier to register, and minimizes queues, effective time without queuing which can improve the quality of New Student registration. This study aims to analyze the Implementation of New Student Admission and the factors that influence New Student Admission. The research paradigm uses constructivism paradigm, case study research design, qualitative research methods with data acquisition techniques by observation and interviews. The results of the study concluded that the implementation of Online New Student Admission greatly facilitates the registration of prospective students in terms of time, data that is accurate, effective and efficient. Even so, there are several shortcomings in the Implementation of New Student Admissions, namely an inadequate internet network, the high cost of the internet network, the number of parents who do not understand Information Technology Science, the lack of maximum socialization regarding New Student Admission such as coordinate points or zoning systems.